PENGGUNAAN PRODUK FERMENTASI DAN KUNYIT DALAM PAKAN TERHADAP PERFORMAN AYAM PEDAGING DAN INCOME OVER FEED AND CHICK COST - -, Nurhayati; Wirawati, Chandra Utami; Putri, Dwi Desmiyeni (Universitas Sam Ratulangi, 2015)
THEÂ UTILIZATION OF FERMENTATION PRODUCT AND CURCUMA IN RATION ON BROILER PERFORMANCE, AND INCOME OVER FEED AND CHICK COST. The aim of this study was to investigate the utilization level of fermentation product combined with curcuma in ration on broiler performace, and income over feed and chick cost (IOFCC). Completely Randomized Design with 4x2x2 factorial arrangement was used in this research. The first factor were levels of fermentation product in ration (0, 10, 20, dan 30%), the second factor were curcuma addition in ration (0% and 2,5%), and the third factor were vaccine applications (without and with vaccine application). The results showed that there were no interaction among the utilization levels of fermentation product, the addition of curcuma, and vaccine applications on broiler performance. The results also indicated that 10% utilization of fermentation product in broiler ration could increase broiler performance (weight gain and feed conversion). 10% utilization of Fermentation product and addition of 2.5% curcuma in ration could produce higher IOFCC compared to control diet. Utilization of fermentation product, curcuma addition in ration, and vaccine application did not affect ration and water consumption. Key words: fermentation product, curcuma, broiler performance, IOFCC.